2002
DOI: 10.1111/j.1749-6632.2002.tb02786.x
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Basis for Implantation Failure in Endometriosis

Abstract: Endometriosis is a benign gynecologic disorder associated with pelvic pain and infertility, with the latter being due, in part, to failure of embryonic implantation in the maternal endometrium. Adequacy of the endometrium for fertility has been classically investigated by histologic evaluation of a mid-late luteal phase biopsy and, historically, normal histology has been reassuring. However, recent studies demonstrate histologically normal, but biochemically abnormal, endometrium during the window of implantat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(72 citation statements)
references
References 76 publications
(69 reference statements)
2
66
0
4
Order By: Relevance
“…4). In humans, the implantation process begins with attachment of the em-bryo to the endometrial epithelium, intrusion through the epithelium and then invasion into the decidualizing stromal compartment, eventually resulting in anchoring of the conceptus and establishment of the fetal placenta and blood supply (5).…”
mentioning
confidence: 99%
“…4). In humans, the implantation process begins with attachment of the em-bryo to the endometrial epithelium, intrusion through the epithelium and then invasion into the decidualizing stromal compartment, eventually resulting in anchoring of the conceptus and establishment of the fetal placenta and blood supply (5).…”
mentioning
confidence: 99%
“…In a study on the molecular mechanism of implantation problem in endometriosis, Giudice et al reported that the products of specific genes were significantly decreased in the endometriosis group compared to the control group in the "window of implantation", which corresponds to the middle period of the secretory stage of the endometrium [8]. These genes were integrin αv and β3, leukemia inhibitory factor (LIF), HOXA-10 and HOXA-11.…”
Section: Discussionmentioning
confidence: 99%
“…It also added that the expression of other genes in the endometriosis group significantly increased during the embryo implantation and such increased expression may be associated with the onset of endometriosis. Further, there was research reporting that endometriosis patients had aberrant expressions of a certain gene associated with the generation of the disease and impact on the abdominal cavity and other tissues and that such patients' normal uterus linings may look histologically normal but were biochemically abnormal [8] [9] [10]. Based on the above research results, it is inferred that relative over-expression or under-expression of certain genes in endometriosis patients' uterus linings may generate the disease itself or hinder embryo implantation during the implantation period.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is a continued need to study novel pathways involved in disease initiation, maintenance, and progression in order to develop better therapies. 1,[4][5][6] We have recently shown that retinoid uptake, metabolism, and action are deficient in endometriotic cells compared to normal endometrial cells. 7,8 We believe that this decreased expression in genes regulating retinoid uptake and action affects differentiation in endometriotic cells.…”
Section: Introductionmentioning
confidence: 99%